Database in Warehouse Automation for Electrical Goods - Sanam, Ezeddin Ali Ahmed (2010)
The database is an integral part use in automation applications. Almost every automation application uses a backend database to store information. This relieves the developer of the application from burden of developing a data store and at the same time makes the application portable as the application can cater to the increase in demand just by changing the back end database. Warehouses are becoming very important with the development of ecommerce. The warehouses that were located closer to the stores for easy accesses have been moved away to remote destinations and the size of the warehouses have increased manifolds due to the increase in demands. Hence the automation of the warehouse operations has become essential to increase the productivity and to meet the customer expectations promptly. This study presents the database design and development for a web based warehouse system management system. The design of the system was carried out according the industry standards using Unified Modeling Language and the prototype was implemented using JSP and Microsoft SQL Server 2005. The system was tested for usability using a sample of real warehouse administrator. Their responses were collected using a detailed questionnaire and analyzed using SPSS 16.0